Analisis Rencana Strategis BPPRD Terhadap Rencana Pembangunan Jangka Menengah Daerah Sumatera Utara - Hamtheldy, Raihan Zaky; Harahap, Muhammad Ikhsan (Universitas Labuhanbatu, 2021)
Strategic Plan (RENSTRA) is the first step to measuring the performance of government agencies, therefore human resources and other resources are needed to be able to answer the demands of the times. To achieve the goals and objectives of the North Sumatra Provincial Tax and Levy Management Agency, appropriate and sustainable operational strategies and policies are needed to achieve the agreed goals.Â Another thing that is also expected in the preparation of the Strategic Plan of the North Sumatra Provincial Tax and Levy Management Agency in 2019-2023 is set with the intention to provide direction as well as guidelines for all officials of the North Sumatra Provincial Tax and Levy Management Agency in building mutual understandings, agreements and commitments to realize the vision and mission of the North Sumatra Provincial Tax and Levy Management Agency on an ongoing basis.Â Realizing synergistic and integrated regional development planning between the North Sumatra Provincial Government and the North Sumatra Provincial Tax and Levy Management Agency and the Regional Revenue Management Technical Implementation Unit as well as the Technical Management Unit of the Regional Revenue Operational Service Center and the Extension Technical Management Unit.